2022
DOI: 10.7150/ijbs.74675
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PPARα mediates FABP1 expression, contributing to IgA nephropathy by stimulating ferroptosis in human mesangial cells

Abstract: Immunoglobulin A nephropathy (IgAN) is the commonest primary glomerulonephritis, and a major cause of end-stage renal disease; however, its pathogenesis requires elucidation. Here, a hub gene, FABP1 , and signaling pathway, PPARα, were selected as key in IgAN pathogenesis by combined weighted gene correlation network analysis of clinical traits and identification of differentially expressed genes from three datasets. FABP1 and PPARα levels were lower in IgAN than control kidney, and line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
(67 reference statements)
0
28
0
Order By: Relevance
“…Previous studies have demonstrated that CYP11B2 [763], FLI1 [764], SLC7A7 [765], NPNT (nephronectin) [766], AZGP1 [767], TREH (trehalase) [768], CCR1 [769], CNTN1 [770], VCAM1 [771] and GBP3 [772] are linked with the development mechanisms of glomerulonephritis. A recent study revealed that FABP1 [773] and NPHS1 [774] expression was altered in IgA nephropathy. CLCN5 [775], ENPEP (glutamylaminopeptidase) [776], CCR1 [777] and NPHS1 [778] have been identified in focal segmental glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CYP11B2 [763], FLI1 [764], SLC7A7 [765], NPNT (nephronectin) [766], AZGP1 [767], TREH (trehalase) [768], CCR1 [769], CNTN1 [770], VCAM1 [771] and GBP3 [772] are linked with the development mechanisms of glomerulonephritis. A recent study revealed that FABP1 [773] and NPHS1 [774] expression was altered in IgA nephropathy. CLCN5 [775], ENPEP (glutamylaminopeptidase) [776], CCR1 [777] and NPHS1 [778] have been identified in focal segmental glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al ( 49 ) demonstrated that histone deacetylase is upregulated in mesangial cells from patients with IgAN and subsequently activates TGF-β/recombinant mothers against decapentaplegic homolog 2/3 (Smad2/3) and Janus kinase 2 (Jak2)/signal transducer and activator of transcription 3 (Stat3) signaling pathways for cellular proliferation and ECM expansion. Gd-IgA1 could also induce mesangial cell ferroptosis by damaging mitochondria and increasing reactive oxygen species and malondialdehyde ( 50 ).…”
Section: Mesangial Cellmentioning
confidence: 99%
“…Some studies revealed that PPARα pathway downregulation reduced FABP1 expression, which led to IgA nephropathy by increasing iron prolapse in human mesangial cells [56]. Other studies indicated that the hub gene, FABP1 and the PPAR signaling pathway were ruled out as being closely related to IgAN [56]. In terms of its mechanism, FABP1 controls GPX4 and ACSL4 through PPAR, which causes IgAN and leads to ferroptosis in the in vitro HMC model of IgAN [56].Therefore, interfering with PPAR signaling to prevent ferroptosis is a possibility for halting or slowing the progression of IgAN [56].…”
Section: Ferroptosis and Ckdmentioning
confidence: 99%
“…Recent evidence has indicated that ferroptosis is an area of progress related to immunoglobulin A nephropathy (IgAN), the most common type of primary glomerulonephritis and a major cause of end-stage renal disease [55]. Some studies revealed that PPARα pathway downregulation reduced FABP1 expression, which led to IgA nephropathy by increasing iron prolapse in human mesangial cells [56]. Other studies indicated that the hub gene, FABP1 and the PPAR signaling pathway were ruled out as being closely related to IgAN [56].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation